Salient Experiences in Student Development: Impact of an Undergraduate STEM Teacher Preparation Program - Sommers, Amie S.; Johnson, Kelly Gomez; Jakopovic, Paula; Rivera, Julio; Grandgenett, Neal; Conrad, John A.; Tapprich, William E.; Cutucache, Christine E. (Frontiers in Education, 2021)
The need for a comprehensive, high-quality pipeline for the development of undergraduate pre-service teachers, especially those that represent a diverse student body, within STEM disciplines is acute. Here, we studied the NoyceSCIENCE program to determine the most impactful experiences offered to undergraduates through the lens of student development theory. We used qualitative coding to analyze data collected from journals (n = 29) written by students of varying backgrounds, and at varying levels within the program (i.e., the Scholar and Intern level) over a 3-year program running period. We observed that faculty mentorship, the ability of undergraduates to mentor others, volunteer experiences, and learning directly from experts had the greatest influence on student development overall. For Scholars that participate for more than 1 year in the program, access to undergraduate mentoring and volunteering experiences contributed most to student development. We posit that these findings are broadly applicable to other science learning communities and STEM content-focused teacher preparation programs as they are program components that can be integrated in isolation or in their entirety.